Global child welfare and well-being - Mapp, Susan C. (New York ; Oxford : Oxford University Press, 2010)
Susan Mapp examines threats to child well-being, investigating violations of the Convention on the Rights of the Child in countries both developed & developing countries. Some problems are well known, such as child trafficking & child soldiers while others are less well known, including unethical adoption practices & the effects of statelessness.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child welfare -- International cooperation; Children's rights